2004
DOI: 10.1002/pi.1725
|View full text |Cite
|
Sign up to set email alerts
|

Vulcanization characteristics and mechanical properties of natural rubber–scrap rubber compositions filled with leather particles

Abstract: Scrap rubber recycling combined with waste leather particles in natural rubber compounds has been studied. The effect of leather and scrap rubber loading on vulcanization characteristics of natural rubber compounds has been evaluated. The presence of leather was found to reduce the scorch time and increase the maximum and minimum torque. While reversion was not observed in the absence of leather at 150 °C, it was more prominent when leather was incorporated. Mechanical properties such as tensile strength, elon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 6 publications
2
47
0
2
Order By: Relevance
“…Although there is a loss of mechanical properties during the process, since the interaction between the vulcanized elastomer and the raw one is generally weak, its recovery may be advantageous when incorporated into new formulations, given the reduction in the cost of the final product, lower consumption of energy and raw materials, and the non-generation of hazardous residues [9][10][11][12][13]. In this way, some authors have studied blends containing at least one phase composed of a recycled elastomer [14][15][16][17][18][19][20] as a viable economic alternative and as an environmentally friendly solution to solid residues, obtaining satisfactory results. Some authors have shown that the vulcanization of blends containing a ground recycled phase is complex [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a loss of mechanical properties during the process, since the interaction between the vulcanized elastomer and the raw one is generally weak, its recovery may be advantageous when incorporated into new formulations, given the reduction in the cost of the final product, lower consumption of energy and raw materials, and the non-generation of hazardous residues [9][10][11][12][13]. In this way, some authors have studied blends containing at least one phase composed of a recycled elastomer [14][15][16][17][18][19][20] as a viable economic alternative and as an environmentally friendly solution to solid residues, obtaining satisfactory results. Some authors have shown that the vulcanization of blends containing a ground recycled phase is complex [14].…”
Section: Introductionmentioning
confidence: 99%
“…12 Before incorporation into the rubber mix, the shavings were neutralized with sodium carbonate (Na 2 CO 3 ), ammonia (NH 3 ), and sodium hydroxide (NaOH). The addition of sodium carbonate and ammonia neutralized chrome shavings to nitrile rubber brought improved dispersion in elastomeric matrix and mechanical properties, whereas sodium hydroxide neutralized shavings exhibited poor properties.…”
Section: Introductionmentioning
confidence: 99%
“…Los resultados mostraron que los compuestos elaborados con los residuos de cuero tratados con urea tienen la menor densidad de entrecruzamiento en comparación al resto de materiales, incluyendo los compuestos elaborados con residuos de cuero sin ningún tratamiento químico previo. En relación al porcentaje de hinchamiento, los compuestos sometidos a tolueno mostraron el mayor grado de hinchamiento, seguido por los compuestos sumergidos en medio alcalino y finalmente el menor grado de hinchamiento fue presentado en los compuestos sumergidos en agua; este comportamiento es interesante en el momento de definir las condiciones a las que estaría expuesto un producto elaborado con estos materiales [52,53].…”
Section: Mezclas De Caucho Con Residuos De Cuero Posindustrialunclassified
“…La dureza y el módulo al 100% siempre fueron superiores en los materiales que contenían residuos de cuero en comparación a los compuestos que no tenían dichos residuos [53].…”
Section: Mezclas De Caucho Con Residuos De Cuero Posindustrialunclassified